The Use of New Dosage Forms of Antibiotics as a Way to Improve the Effectiveness and Safety of Antibiotic Therapy - S. K. Zyryanov; E. A. Baibulatova (Антибиотики и Химиотерапия, 2020)
The Issue of optimizing the dosage regimens of antibacterial medications is particularly important due to the high relevance of the problem of antibiotic resistance, as well as the limited development of new antibiotics for outpatient practice. The article discusses the pharmacokinetics of amoxicillin and amoxicillin/clavulanate for oral administration; the authors propose to optimize the use of these antibiotics by using them in the dosage form of dispersible tablets under the trademark Solutab®. This dosage form has higher bioavailability of active substances, which can be compared to injectable preparations, as opposed to traditional dosage forms such as film-coated capsules and tablets. The optimized pharmacokinetic profile of these medications can contribute to higher clinical efficacy and tolerability of antibiotic therapy, as well as reducing the spread of antibiotic resistance. A review of the results of clinical studies confirming the higher efficacy and favorable safety profile of antibiotics in this dosage form in both adults and children in the treatment of respiratory infections is presented. The use of amoxicillin in dispersible tablets has demonstrated higher efficacy in the treatment of acute streptococcal tonsillitis. A more pronounced dynamics of resolving the clinical symptoms of acute bacterial sinusitis was noted when using amoxicillin/clavulanate in the form of dispersible tablets, as well as a lower incidence of adverse effects, including in the gastrointestinal tract, compared with film-coated tablets. Dispersible tablets are convenient because they can be dispersed in water and administered as a suspension, which is especially important in patients with dysphagia, as well as in children and the elderly, who find it difficult to swallow the treatment of acute bacterial sinusitis has demonstrated pharmacoeconomic advantages compared with other solid oral dosage forms. Thus, the use of antibiotics in dispersible tablets can help increase the effectiveness, tolerability, and convenience of the therapy, reduce the cost of treatment, as well as slow down the growth of antibiotic resistance.